Molecular characterization and phylogenetic analysis of FLA from different water sources in Egypt. (20th January 2022) - Shawkey, Lamiaa A.; Elfeky, Faten A.; Abou-Elnour, Basma M.; El-Wakil, Eman S.
Abstract: Free-living amoebae (FLA) are protozoa ubiquitously found in nature. In addition to their natural distribution, some species have been documented as pathogenic to humans. The main aim of the current study was the molecular identification, sequencing and phylogenetic analysis of morphologically detected FLA in water sources in El-Qalyubia, Egypt. A total of 96 water samples were collected from different water sources. Each water sample was filtrated and cultured on non-nutrient agar (NNA). Morphologically positive FLA were subjected to PCR, PCR products were sequenced and the obtained sequences were phylogenetically analysed. FLA were found in 41 water samples examined (42.7%). Nile water and groundwater were the sources with the highest prevalence rates (83.3 and 62.5%, respectively). Naegleria italica was first identified in Egypt from the waters of the Nile. In addition, Vahlkampfia spp. and Hartmannella spp. were also detected. However, other FLA species, including Acanthamoeba spp. and the pathogenic Naegleria fowleri, previously reported in Egypt, were not included in this study. The recent identification of these FLA in the Egyptian waters related to human populations indicates the need for more phylogenetic studies using larger sample sizes to investigate their potential threat to human health. HIGHLIGHTS: This study documented the presence of FLA in different water sources in El-Qalyubia, Egypt. Naegleria italica was identified for the first time in Egypt from the waters of the Nile. Besides, Vahlkampfia spp. and Hartmannella spp. were also detected. This study presents knowledge of the prior prevalence of FLA that should be considered by the clinicians and the environmental professionals in the region.